(untitled) (Research, Society and Development, 2020)
Aedes aegypti is the um mosquito responsible for the transmission of several diseases to humans such as dengue, chikungunya, Zika virus and urban yellow fever. The control of this culicid is done by utilizing insecticides that cause insect resistance. Therefore, natural alternatives to control A. aegypti have been sought. Thus, the objective of our work was to characterize the chemical composition of the crude extract of the leaves of Inga laurina and to evaluate the insecticidal activity of the extract on the larvae of A. aegypti. The crude extract was prepared form dry leaves by dynamic maceration using alcohol 96º GL as extracting solvent. The chemical identification of the compounds found in the crude extract was done by a gas chromatography coupled to mass spectrometry. The larvicidal activity was determined by larval packet test in third-stage development larvae A. aegypti. Fifteen compounds were identified in the leaves and the major ones were γ- sitosterol (34.39%), phytol (14.51%), squalene (8.57%) and stigmasterol (7.38%). I. laurina leaf crude extract presented larvicidal activity potential against A. aegypti larvae presenting lethal concentration of 50% (CL50) of 0.98 mg/mL and 99% (CL99) of 2.69 mg/mL. Thus, I. laurina leaf crude extract presented rich composition of phytosterols and promising insecticide activity against A. aegypti larvae, offering new possibilities for the application and development of products.